Improved Productivity of Streptomyces mobaraensis Transglutaminase by Regulating Zymogen Activation - Yin, Xiaoqiang; Rao, Shengqi; Zhou, Jingwen; Du, Guocheng; Chen, Jian; Liu, Song (Frontiers in Bioengineering and Biotechnology, 2022)
Streptomyces mobaraensis transglutaminase (TGase) is extracellularly expressed as a zymogen and then activated by TGase-activating protease (TAP). In this study, we reported the strategy for improving TGase production via the regulation of TAP activity in S. mobaraensis. First, we analyzed the effects of three inorganic nitrogen sources on TGase production. With 30 mM nitrogen content, the time to the peak of TGase activity induced by (NH4)2SO4 or NH4Cl was 72 h, 12 h earlier than that of the fermentation without adding NH4+. SDS-PAGE analysis indicated that NH4+ accelerated the TGase activation in S. mobaraensis. Then, we examined the effect of NH4+ on the TAP biosynthesis using a TGase-deficient S. mobaraensis strain. It was showed that NH4+ enhanced the TAP activity at the early stage of the fermentation, which was dependent on the concentration and time of NH4+ addition. Last, the yield and productivity of S. mobaraensis TGase were respectively increased by 1.18-fold and 2.1-fold when the optimal NH4+ addition (60 mM and 12 h) was used. The fermentation period was shortened from 84 h to 48 h. The NH4+ addition also increased the storage stability of crude enzyme at the room temperature. These findings will benefit the TGase production and its activation mechanism in S. mobaraensis.